Oil-related kidnapping in the Niger Delta region - Omotola, J. Shola (The political economy of kidnapping and insecurity in Nigeria, 2024)
Niger Delta is the core region for oil and gas production, which is the mainstay of Nigeria’s economy. Yet, the region is a major conflict theatre, where several militant and criminal groups have emerged in support of popular uprising against oil-induced environmental crisis. This region that is dominantly inhabited by minority ethnic groups has equally emerged in resistance of ethno-politics of majoritarian dictatorship, which has turned it into a mere extractive site without commensurate development. Amidst these, kidnapping has emerged as one of the tactics and strategies employed to advance greed and grievances of militant and criminal groups in the Niger Delta region, with negative consequences for both the state and society. Accordingly, this chapter examines the manifestation, causes and consequences of oil-related kidnapping in the Niger Delta region of Nigeria.